2019
DOI: 10.1021/acs.jpcc.9b06327
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-Driven Formation of 2D Nanoporous Networks on Metal Surfaces

Abstract: Controlling the quantum confinement of (spin-dependent) electronic states by material design opens a unique avenue to accelerate the implementation of quantum technology in next generation photonic and spintronic applications. In the nanoworld, two-dimensional porous molecular networks have emerged as highly tunable material platform for the realization of exotic quantum phases for which the nanopores can be tuned by chemical functionalization of the size and shape of the molecules. Here, we demonstrate a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…We calculate the pair potential between the molecules using partial charges on each atom in the molecules obtained from the RASSCF calculation of the ground state of CuPc t-1 and the ionized state of CuPc + t1 (20). Such a pair-potential calculation was previously applied to similar molecular systems (22)(23)(24). As a result, it is found that depending on the initial in-plane orientation of the molecules relative to their unit cell (angles marked in Fig.…”
Section: Structural Dynamics From Wavefunction and Xpd Pattern Analysismentioning
confidence: 99%
“…We calculate the pair potential between the molecules using partial charges on each atom in the molecules obtained from the RASSCF calculation of the ground state of CuPc t-1 and the ionized state of CuPc + t1 (20). Such a pair-potential calculation was previously applied to similar molecular systems (22)(23)(24). As a result, it is found that depending on the initial in-plane orientation of the molecules relative to their unit cell (angles marked in Fig.…”
Section: Structural Dynamics From Wavefunction and Xpd Pattern Analysismentioning
confidence: 99%